Effect of LED Spectrum on the Quality and Nitrogen Metabolism of Lettuce Under Recycled Hydroponics - Li, Jie; Wu, Tao; Huang, Ke; Liu, Yubing; Liu, Mingyue; Wang, Junwei (Frontiers in Plant Science, 2021)
Light quality optimization is an efficient method for improving the growth and quality of lettuce in plant factories. In this study, lettuce seedlings were illuminated under different light-emitting diode (LED) lights, namely, red-bule (RB), red-blue-green (RBG), red-blue-purple (RBP), and red-blue-far-red (RBF) LED lights, to investigate the effect of light quality on growth, quality, and nitrogen metabolism. The combination of 75% red and 25% blue light was set as the basic light source, and 20% of green, purple and far-red light were added to basic light source, respectively. All the treatments were set to 200 μmol·m−2·s−1. Results showed that the fresh weight and dry weight of aboveground lettuce under RBG, RBP, and RBF treatments were significantly lower than those under the RB treatment because of the decrease in the effective photon flux density for chlorophyll absorption. The vitamin C content of the lettuce leaves was increased by about 23% with the addition of purple light. For nitrate reduction, the addition of green light significantly increased the nitrite content of the lettuce leaves. It also promoted the reduction from nitrite to ammonium through the activation of the nitrite reductase (NiR) expression and enzyme activity. The nitrate and ammonium content decreased with the addition of purple light because of the inhibited NR and NiR expression and enzyme activity. For nitrogen assimilation, individual (e.g., Asp, Glu, and Leu) and total amino acids were induced to increase by adding green, purple, and far-red light. The addition of light was hypothesized to have inhibited protein biosynthesis, thereby causing the accumulation of amino acids. Correlation analysis showed that the relative expression levels between HY5 and NR/NiR presented a significantly negative correlation. Transcription factor HY5 might mediate the regulation of light quality on nitrogen metabolism by inhibiting NR and NiR expressions. It might also exert a negative effect on nitrate reduction. Further studies via genome editing techniques on the identification of HY5 functions for nitrate assimilation will be valuable. Nevertheless, the results of this work enrich the understanding of the effect of light quality on nitrate metabolism at the level of gene expression and enzyme activity.